GE_GERICHTE A/231/2024 vom 19. August 2024 - GE Cour de justice (2024)
IMPÔT SUR LA FORTUNE;ACTION(PAPIER-VALEUR);VALEUR FISCALE;SOCIÉTÉ HOLDING;EFFET CONFISCATOIRE DE L'IMPÔT | LHID.14.al1; LIPP.49.al1